Analysis of SLITRK1 in Japanese patients with Tourette syndrome using a next-generation sequencer. (December 2015) - Inai, Aya; Tochigi, Mamoru; Kuwabara, Hitoshi; Nishimura, Fumichika; Kato, Kayoko; Eriguchi, Yosuke; Shimada, Takafumi; Furukawa, Masaomi; Kawamura, Yoshiya; Sasaki, Tsukasa; Kakiuchi, Chihiro; Kasai, Kiyoto; et al.
Abstract : The SLITRK1 ( Slit and Trk-like 1 ) gene has been suggested to be a promising candidate for Tourette syndrome (TS) since the first report that identified its two rare variants adjacent to the chromosome inversion in a TS child with inv(13) (q31.1;q33.1). A series of replication studies have been carried out, whereas the role of the gene has not been elucidated. The present study aimed to determine whether the two or novel nonsynonymous variants were identified in Japanese TS patients and carry out an association analysis of the gene in a Japanese population. We did not observe the two or any novel nonsynonymous variants in the gene. In contrast, a significant difference was observed in the distributions of the haplotypes consisting of rs9546538, rs9531520, and rs9593835 between the patients and the controls. This result may partially support the implication of SLITRK1 in the pathogenesis of TS, warranting further studies of the gene.